Design and stability analysis of a super‐twisting controller for a PS‐FBC–based fuel cell module. Issue 1 (14th November 2019) - Anderson Azzano, Jorge L.; Moré, Jerónimo J.; Puleston, Paul F.
Abstract: Proton‐exchange membrane fuel cells have been established as a really promising technology, specially due to their high efficiency and scalability features, additionally to their low pollution emissions. In a typical topology, fuel cell module (FCM) is usually integrated into a hybrid power system, where the FCM is designed to satisfy the main power requirements and reduce the current ripple at the fuel cell output. In this framework, the aim of this paper is to analyze and design a sliding mode control (SMC) for a FCM based on an isolated phase‐shifted full bridge converter. This particular topology provides a high conversion ratio and attains a reduction of switching losses, which allow its application in low and medium power systems. From the control viewpoint, the proposed module represents a challenge due to the highly nonlinear behavior and wide operation range of the FCM, together with system parameter uncertainties and perturbations. To solve these issues, a second‐order sliding mode super‐twisting algorithm (STA) is proposed. As its main advantage, the STA reduces significantly the control chattering while preserving several features of conventional SMCs, such as robustness and finite time convergence. In order to analyze the zero dynamics stability, a Lyapunov study is proposed, taking advantage of its particular Liérnad‐type system structure. Finally, the designed algorithm is thoroughly analyzed and validated by computer simulation on a commercial 10‐kW FCM and compared to first‐order SMC. Abstract : This paper analyzes and designs a second order sliding mode control for a FCM based on an isolated phase‐shifted full bridge converter. To guarantee the stability of the controlled system, the zero dynamics stability is studied through a special Lyapunov function, taking advantage of its particular Liérnad‐type system structure. The proposed controller proves to successfully attain robust tracking of the power reference, in spite of variable power demand, voltage bus variations, and system parameters uncertainties.